Multi-inch single-crystalline perovskite membrane for high-detectivity flexible photosensors - Liu, Yucheng; Zhang, Yunxia; Yang, Zhou; Ye, Haochen; Feng, Jiangshan; Xu, Zhuo; Zhang, Xu; Munir, Rahim; Liu, Jia; Zuo, Ping; Li, Qingxian; Hu, Mingxin; et al. (Nature communications, 2018)
Single crystalline perovskites exhibit high optical absorption, long carrier lifetime, large carrier mobility, low trap-state-density and high defect tolerance. Unfortunately, all single crystalline perovskites attained so far are limited to bulk single crystals and small area wafers. As such, it is impossible to design highly demanded flexible single-crystalline electronics and wearable devices including displays, touch sensing devices, transistors, etc. Herein we report a method of induced peripheral crystallization to prepare large area flexible single-crystalline membrane (SCM) of phenylethylamine lead iodide (C 6 H 5 C 2 H 4 NH 3 ) 2 PbI 4 with area exceeding 2500 mm 2 and thinness as little as 0.6 μm. The ultrathin flexible SCM exhibits ultralow defect density, superior uniformity and long-term stability. Using the superior ultrathin membrane, a series of flexible photosensors were designed and fabricated to exhibit very high external quantum efficiency of 26530%, responsivity of 98.17 A W −1 and detectivity as much as 1.62 × 10 15 cm Hz 1/2 W −1 (Jones). Hybrid halide perovskite single crystals show excellent optoelectronic properties but their small size and large thickness limit their application. Herein Liu et al. grow large area ultrathin flexible crystalline membrane of layered perovskite and demonstrate high detectivity in the flexible photosensors.